(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Adolescence is a phase of rapid growth and development characterized by significant physical, physiological, and behavioural changes. In India, the prevalence of underweight among adolescent females aged 15 to 19 is 47%. Undernutrition can be compared to Karshya described in Ayurvedic classics. The proposed trial drug, Drakshadi Lehya, is a classical formulation mentioned in Ashtanga Hridaya under Pandu Roga Chikitsa, appears to be safe and potent in managing the condition. The study design was quasi experimental study with a sample size of 20 underweight adolescent girls, each for the study and control group aged between 10 and 19 years with a body mass index (BMI) less than 18.5kg/m2 were selected from the Outpatient Department of Swasthavritta, Govt. Ayurveda College Panchakarma Hospital, Poojappura, Thiruvananthapuram. Subjective parameters assessed were the cardinal signs and symptoms of Karshya as mentioned in the Brihathrayee. The objective parameters were body mass index, mid-arm circumference, and waist-hip ratio, which were analysed before the study (0th day), after the study (45th day), and after the follow up (75th day). The study group was instructed to take 12 grams of Drakshadi Lehya twice daily after meals for 45 days, along with dietary modifications based on their nutritional needs. The control group was given advice regarding dietary modifications only. The statistical analyses, using Friedman’s test and pairwise comparisons, consistently showed highly significant changes in the study group (p<0.001 in most cases) and often less significant or non-significant changes in the control group. This pattern of results strongly supports the efficacy of the intervention. After the study, the statistical interpretation suggest that Drakshadi Lehya is an effective formulation in underweight adolescent girls.